SOSIALISASI BADAN USAHA MILIK DESA (BUMDES) BAGI PERANGKAT DESA BAROS - Akhmad Saebani; Dewi Darmastuti; Agus Maulana; Andy Setiawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Baros Village is a village located in Serang Regency, Banten. Baros Village is dominated as an agricultural area so that the economic activity of the majority of the population is in the agricultural and trade sectors. The education level of the majority of Baros villagers is high school graduates/equivalent and only approximately 5% of the population has a bachelor's degree. The weakness of Baros Village's economic activity is that there is no Village Original Income (Pendapatan Asli Desa/PADes). This is due to the absence of sources of village financial income that can be generated by operations from the village itself such as Village-Owned Enterprises (BUMDes), and also the lack of motivation and awareness of the village community to have BUMDes. In this community service activity, Baros Village officials will be given socialization and understanding of BUMDes. This activity was carried out by discussing the process of establishing and managing BUMDes by exploring the resources owned by Baros Village. With the socialization of BUMDes it is hoped that it can motivate village officials and communities to establish BUMDes and have an understanding of BUMDes governance so that in the end the Baros Village can generate Village Original Income (PADes), so that it can improve the welfare of the Baros villagers